Human health risk of heavy metal biomagnification: Trophic transfer patterns in aquatic ecosystems - Naz, Saira; Habib, Syed Sikandar; Arshad, Madeeha; Majeed, Saima; Acar, Ümit; Kesbiç, Osman Sabri; Mohany, Mohamed; Aragona, Francesca; Fazio, Francesco (Elsevier BV, 2025)
Background: Heavy metal contamination in aquatic ecosystems poses significant ecological and human health risks, particularly through trophic transfer in food webs. Objective: This study investigates the mean concentrations and trophic transfer of heavy metals (Cd, Cu, Cr, and Pb) across various environmental compartments (water, sediment, plankton) and trophic levels (three fish species: Catla. catla, Labeo rohita, and Cyprinus carpio) in an aquatic ecosystem. Methodology: Samples were collected in 2024 and heavy metals in the samples were determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). Results: Cu was most abundant in water (1.5–2.0 μg/L) and sediments (20–25 μg/g DW), while plankton accumulated high Cu and moderate Pb and Cr levels. Among fish, C. carpio showed the highest metal accumulation. Trophic magnification factor (TMF), which quantifies metal concentration trends across food chains, indicated biomagnification of Pb (TMF = 1.56) and Cd (TMF = 1.31), and biodilution of Cu (TMF = 0.64) and Cr (TMF = 0.73). Biomagnification factor (BMF), reflecting metal transfer from prey to predator, was highest for Pb in C. carpio (BMF = 3.89). Principal Component Analysis showed Cu and Pb enriched in sediments, while Cd was associated with plankton, indicating bioavailability at lower trophic levels. Although hazard index (HI) values were below the safety threshold for all fish species, C. carpio posed higher health risks due to elevated Cd and Pb levels. Conclusions: Overall, the study reveals significant biomagnification of Pb and Cd, posing ecological and health risks, while Cu and Cr show biodilution. Mitigation requires integrated management, including source control, monitoring, ecological remediation, and public awareness.
Keywords: Aquatic ecosystem, Bioaccumulation, Biomagnification, Fish species, Heavy metals, Trophic transfer